Synthesis of γ-Amino Esters by Copper-Catalyzed Intermolecular 1,2-Aminoalkylation of Alkenes with Amines and α-Bromoalkyl Esters - Pan, Gao-Hui; Song, Ren-Jie; Xie, Ye-Xiang; Luo, Shenglian; Li, Jin-Heng (Synthesis, 2018)
A new copper-catalyzed intermolecular 1,2-aminoalkylation of alkenes with α-bromoalkyl esters and amines for the synthesis of γ-amino esters is described. Employing the Cu(OTf)2 and 2,2′-bipyridine catalytic system, the three-component reaction allows the formation of two new chemical bonds, including one C–C bond and one C–N bond, in a single reaction, and represents a new alkene difunctionalization using a radical strategy.
Keywords: copper; aminoalkylation; alkenes; γ-amino esters; α-bromoalkyl esters